Effect of some chemical pesticides and plant extracts on hard ticks Hyalomma anatolicum anatolicum on cows and buffaloes in Basrah governorate - Faisal Alsaedi, Ghazwan; Alwan Salmen, Muhammd; Safaih Shenawa, Majed (University of Thi-Qar Journal, 2022)
The study evaluated the effect of some chemical pesticides and plant extracts against hard ticks (Ixodidae) that infested cows and buffaloes.The results showed that Actapoor SL2 % exceeded Mlathion SL1% in delivering the highest mortality ratio, reaching (98.26% and 69.86%) respectively. The highest mortality ratio of Actapoor SL2 % (99.74%) was recorded at a concentration of 5% compared to Mlathion SL1%, which recorded its highest mortality ratio (74.93%) at 100 % concentration. The results showed significant differences among plant extracts in the effectiveness against ticks. The highest mortality percentage (11.82 %) was recorded using chinaberry extract. In comparison, the extracts of Indian Privet and eucalyptus had the lowest mortality percentages of (4.37% and 2.39%) respectively. There were no significant differences with regard to the concentrations and the treatment periods that were used to apply the plant extracts.